Mastery of English vocabulary trough pop up method - Aba, La; Pontoh, Meylan (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
Mastering of vocabulary is part of mastering a language, especially English, because if someone mastered the language, it means that person mastering of vocabulary. In other words, the more vocabulary students have the easier for students to compose words and communicate well. Such as learning English they say that the main reason was found difficulties to understand the lesson and the solution to all of these problems was the teachers should make learning media as attractive as possible the can, so that they can attract students to make small notes for the vocabulary they get from media learning. Besides, the teacher can motivate students to be more active in adding new vocabulary trough pop up method. In this research using a qualitative method in which the process of research was observed the students vocabulary. In the results of this study was the weakness of vocabulary mastering in high school. Teachers also was implemented several methods in order to help students in the process of mastering words. Not only the Teacher, but also the researcher suggests several methods to be used so that students can easily understand English quickly.